IDENTICAL HIV-1 PROVIRUSES ORIGINATE FROM CELL PROLIFERATION OR INFECTION WITH A COMMON VIRAL ANCESTOR - Niyongabo, Aurelie (My University, 2020)
Understanding the mechanisms for HIV-1 persistence during antiretroviral therapy (ART) is crucial for developing curative strategies. Due to the high intra-patient genetic diversity of HIV-1, I hypothesized that integrated HIV-1 DNA (proviruses) with identical sub-genomic sequences are sustained during ART through cellular proliferation. To test this hypothesis, a method called “Multiple-Displacement Amplification Single-Genome Sequencing” (MDA-SGS) wherein the site of proviral integration in the host genome and the full-length HIV-1 sequence can be determined, was applied to 34 sets of proviruses with identical P6, protease, reverse transcriptase (P6-PR-RT) sequences in a single donor with viremia suppressed on ART reported by Musick, et al(1). The MDA-SGS workflow includes the isothermal amplification of DNA from cells containing single proviruses of interest within their sites of host integration followed by integration site analysis on the products to determine if proviruses identical in P6-PR-RT also have identical integration sites and, therefore, result from the proliferation of a single infected cell. If different sites of integration are observed, then I conclude that the identical proviruses result from infection of two or more different cells by a closely related viral ancestor. Of the 20 populations of proviruses with identical P6-PR-RT sequences successfully assayed by MDA-SGS, I found 9 to contain only identical integration sites (cell clones), 6 to have only unique integration sites (infection with a common ancestor), and 5 to contain a combination. The finding that proviruses identical in P6-PR-RT often have different sites of integration suggests infection of multiple cells prior to ART or during an ART interruption with a common viral ancestor, each establishing a latent infection allowing them to survive and, likely, divide. Targeting such long-lived, infected, proliferating cells is necessary to achieve HIV-1 remission without ART.
Keywords: Human Immunodeficiency Virus Type-1 (HIV-1); Proviral Structures; Whole Genome Sequencing; Integration Site Analysis